Nigella sativa and health outcomes: An overview of systematic reviews and meta-analyses - Li, Zhongyu; Wang, Yang; Xu, Qing; Ma, Jinxin; Li, Xuan; Yan, Jiaxing; Tian, Yibing; Wen, Yandong; Chen, Ting (Frontiers in Nutrition, 2023)
Background: Nigella sativa (N. sativa) consumption has been associated with various health outcomes; however, no review articles summarizing these reports. Objectives: This overview of systematic reviews and meta-analyses aimed to evaluate the scientific literature available on the association between N. sativa and health outcomes. Methods: PubMed, Cochrane Library, Embase and Scopus databases were searched from inception to September 30, 2022. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2009 statement, Assessment of Multiple Systematic Reviews (AMSTAR) 2 checklist and Grades of Recommendations, Assessment, Development and Evaluations (GRADE) systems were used to assess the reporting quality, methodological quality, and evidence quality for each meta-analysis, respectively. The results were synthesized in a narrative form. Results: This overview included 19 eligible meta-analyses, which published in peer reviewed journals from 2013 to 2021. The overall methodological quality was relatively poor, only one moderate quality, three low quality, 15 critically low quality. For reporting quality, the item two, item five, item eight, item nine, item 15 and item 24 need to improve. And among the 108 outcomes indicators of the quality of evidence, five were graded as moderate quality, 17 were graded as low-quality and 86 were graded as very low-quality evidence. The risk of bias, inconsistency and imprecision were the main downgrading factors. Conclusion: This overview suggested that the N. sativa was beneficial for a variety of clinical outcomes, but it needs to improve the reporting quality and methodological quality. In addition, the clinical effects of N. sativa need to be confirmed through high-quality randomized controlled trials.